Diagnosis and treatment of infection with Brucella abortus, biotype 5. Issue 2 (March 1967) - Robertson, L.
Abstract : A case of brucellosis due to Brucella abortus, biotype 5, occurred in a bulk milk-tanker driver who collected milk from refrigerated tanks on 23 farms. The organism was isolated from blood cultures by using a serum dextrose broth containing antibiotics. Serological investigations indicate that both abortus and melitensis antigen suspensions should be used in the investigation of cases of suspected brucellosis. As Brucella abortus is an intracellular parasite heavy, prolonged, antibiotic therapy is necessary in the treatment of the disease. The danger of inadequate treatment of the acute disease is that it may become chronic, and response to antibiotic therapy in chronic brucellosis is not good.